Management consulting : a guide to the profession - Kubr, Milan; Kubr, Milan; International Labour Office (Geneva : International Labour Office, 2002)
This is a widely recognized reference work on the state of the art of management consulting. It offers an extensive introduction to consulting: its nature, professional standards, intervention methods, behavioural rules, current developments and future perspectives.
10.1 The consultant's role in implementation10.2 Planning and monitoring implementation; 10.3 Training and developing client staff; 10.4 Some tactical guidelines for introducing changes in work methods; 10.5 Maintenance and control of the new practice; Chapter 11 Termination; 11.1 Time for withdrawal; 11.2 Evaluation; 11.3 Follow-up; 11.4 Final reporting; Part III CONSULTING IN VARIOUS AREAS OF MANAGEMENT; Chapter 12 Consulting in general and strategic management; 12.1 Nature and scope of consulting in corporate strategy andgeneral management; 12.2 Corporate strategy.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Business consultants; Consultants; Conseillers d'entreprise.; REFERENCE -- Questions & Answers; BUSINESS & ECONOMICS -- Consulting; Business consultants; Organisatieadvisering; Conseil en gestion; Formation (Éducation); Gestion; Perfectionnement; Société de conseil; Guide (Descripteur de forme)